PENERAPAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT UNTUK MENINGKATKAN PRESTASI BELAJAR IPA SISWA SMP - Ernalem Tarigan; Elisabet Br. Gurusinga (Jurnal Dedikasi Pendidikan, 2021)
The low achievement of students in science lessons, especially in food biotechnology material has long been a burden on the minds of researchers, many students cannot explain properly and correctly. In the evaluation, many student scores are below the KKM. Teachers still use conventional learning so that the classroom atmosphere becomes passive, this is because students are less enthusiastic and not ready to take lessons. This classroom action research aims to determine the application of the Cooperative Script learning model in improving student achievement. This research was carried out using descriptive qualitative methods and class action research approaches, which were carried out in 2 cycles. Each cycle includes planning, implementation, observation and reflection. The subjects of this classroom action research were students of class IX-3 even semester of SMP Negeri 2 Deli Tua. From the research conducted, it can be seen that there is an increase in learning outcomes achieved by students in mastering the material. Based on data analysis, it can be concluded that in cycle 1, students' learning completeness on this material average value is only 69.29, while in cycle 2 by applying the learning strategy Cooperative Script learning model increases in cycle 2 the average value increases to 87.14. Student responses also increased, data from observations on student activities from 52.08% in cycle 1, increased in cycle 2 to 89.58%..